TRIVALENT ION CROSS-LINKED AND ACETALATED GELLAN GUM MICROSPHERES OF GLIMEPIRIDE - DAS, SUDIPTA; DEY, RIMI (Asian Journal of Pharmaceutical and Clinical Research, 2020)
Objectives: A novel formulation was developed with glimepiride loaded trivalent ion Al+3 cross-linked and acetalated gellan gum microspheres. Methods: The glimepiride loaded microspheres were formulated using sodium alginate and gellan gum. Cross-linking agents used for the microspheres were aluminum chloride (AlCl3) and glutaraldehyde (GA). The evaluation processes of prepared microspheres were carried out by in-vitro release study, swelling index, microscopic analysis, and entrapment efficiency. Results: All the formulations show good entrapment efficiency and the maximum entrapment 84.6% was governed by the formulation (F3) cross-linked by AlCl3 and GA and their obtained mean particle size were 12.46±3.21 μm. Release profile of the formulations revealed the sustained design of the drug, particularly this formulation (F3), releasing approximately 40% over 4 h. Conclusions: From this experiment, it can be accustomed that F3 possesses higher standard formulation than the rest due to good release profile and entrapment efficiency. Therefore, the long term stability study is required for future development of this formulation.